Artabotrys brachypetalus Benth.: potencial antifúngico, antibiofilme e antivirulência frente a patógenos de interesse em saúde pública e avaliação da toxicidade em Caenorhabditis elegans - Siqueira, Camila de Paula (2022)
The oral mucosa is composed of several microorganisms such as bacteria and yeasts, when they get out of balance, these can cause infections. Pathogenic microorganisms have the ability to form biofilms on a hard surface like as teeth, causing inflammatory processes that can spread to other organs through the bloodstream, these infections are aggravated in immunocompromised and hospitalized patients. Still some isolates have the ability to produce important virulence factors that favor the infectious process and make treatment difficult, such as enzyme expression. This difficulty implies the use of drugs for long periods, inducing resistance to the usual drugs, in addition to high toxicity to the host, which makes treatment difficult. In this context, Artabotrys brachypetalus Benth. has been used in folk medicine for the treatment of some diseases such as bacterial infections, malaria, larvicide, lymph node swelling, among others through infusions with bark, root and leaves of the plant. The use of natural products provides us with an effectiveness in the treatment of infections with minimized. The objective of this study was to analyze the effectiveness of the root extract and fractions of A. brachypetalus against bacteria to causing caries and periodontal disease and Candida sp. Minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) and minimum fungicide concentrations (MFC) and the ability to inhibit and/or eradicate preformed biofilm in extracts with MIC < 100µg/mL and >1000µg/mL were evaluated. The ability to reduce and/or inhibit exoenzymatic expression by Candida sp. Finally, the toxicity of the samples was analyzed using the methodology of C. elgans. The L-CMS analysis of the most active fractions revealed the presence of metabolites such as alkaloids, flavonoids, terpenes and fatty acids. The ethanolic extract of the root showed the best results, being CFM fungicidal for C. glabrata with MIC and CFM of 375 µg/ml. For inhibition of biofilm formation, CIMB50 and IC50 of 1.46 and 1.59 µg/ml were obtained against C. glabrata, while biofilm eradication resulted in IC50 of 0.00028 µg/ml against C. tropicalis. By promoting the expression of reducing exoenzymes (½MIC) from the samples, or root extract, a significant hemolytic activity of 42.7% (p ≤0.03) against C. albicans. For phospholipase a 15.03% (p ≤ 0.03) reduction of phospholipase to dichloromethane against C. albicans. For proteinase, reduction of 35.8% (p ≤ 0.03) against C. tropicalis. The ethanolic extract of the root showed survival above 50% at concentrations above 1000µg/mL. We can conclude that the extracts and fractions of A. brachypetalus show low toxicity in assays performed with C. elegans and high antifungal, antibiofilm and antivirulence potential against Candida sp.